2017
DOI: 10.2351/1.4989766
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the laser power to prevent hot cracking during laser welding of tempered steel

Abstract: It is shown that a temporal modulation of the laser power can prevent the formation of hot cracks during deep-penetration laser welding of tempered steel. For this purpose, the influence of the modulated laser power on the cumulated length of the hot cracks in the weld seams was quantified. Varying amplitude and frequency of the modulation significantly changes the pattern and length of the hot cracks. Moreover, hot cracks can be prevented entirely in a specific range of the modulation frequency that depends o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…1b) [9]. In different fields of laser manufacturing, greater control over the power temporal emission profiles allowed to solve defect formation issues such as hot cracks or porosity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…1b) [9]. In different fields of laser manufacturing, greater control over the power temporal emission profiles allowed to solve defect formation issues such as hot cracks or porosity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The authors noticed enhanced removal of material in the kHz regime and suggested that oscillation modes can play a role in ejection but did not provide any detailed explanations. Melt pool surface waves effects were studied in welding for common metals and have been shown to reduce metal porosity 22 , prevent hot cracking 23 and increase keyhole stabilities 24 . While evidence was presented in some of these studies to support the positive effects of periodic modulation, the underlying physics and broader impact on other observables, most notably molten liquid ejection, is far from complete.…”
Section: Introductionmentioning
confidence: 99%
“…Schaefer et al [15] reduced the hot cracks formation in steel by modulation with laser power. However, additional investigation is still needed to clarify the interaction between the weld pool geometry, the thermally induced tensile stresses, and the strain in the weld zone.…”
Section: Introductionmentioning
confidence: 99%